2022
DOI: 10.1038/s41418-022-01094-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and cell death-associated inflammation

Abstract: Mitochondria have recently emerged as key drivers of inflammation associated with cell death. Many of the pro-inflammatory pathways activated during cell death occur upon mitochondrial outer membrane permeabilization (MOMP), the pivotal commitment point to cell death during mitochondrial apoptosis. Permeabilised mitochondria trigger inflammation, in part, through the release of mitochondrial-derived damage-associated molecular patterns (DAMPs). Caspases, while dispensable for cell death during mitochondrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 120 publications
1
46
1
Order By: Relevance
“…It was found that the synthesized berberines did not affect the mitochondrial membrane potential ( Ψ m ) in isolated rat liver mitochondria, suggesting no negative impact on the functioning of organelles crucial to cell viability. 86–88 Furthermore, these investigated compounds did not influence the survival of both normal (HEK-293) and tumor-derived SH-SY5Y cells (IC 50 > 0.1 mM).…”
Section: Resultsmentioning
confidence: 91%
“…It was found that the synthesized berberines did not affect the mitochondrial membrane potential ( Ψ m ) in isolated rat liver mitochondria, suggesting no negative impact on the functioning of organelles crucial to cell viability. 86–88 Furthermore, these investigated compounds did not influence the survival of both normal (HEK-293) and tumor-derived SH-SY5Y cells (IC 50 > 0.1 mM).…”
Section: Resultsmentioning
confidence: 91%
“…Mitochondrial dysfunction and associated excessive levels of mtROS are major supporters of inflammation [ 32 ] that drive the pathogenesis of many diseases, including neurodegenerative disorders, cancer, viral and bacterial infections, cardiovascular diseases, metabolic syndromes, and autoimmune disorders [ 31 ].…”
Section: Inflammation: An Overviewmentioning
confidence: 99%
“…Inflammasomemediated and redox-sensitive inflammatory pathways act synergistically, potentially potentiating the inflammatory response. [114,115] Fujioka et al found that secondary inflammatory responses may be a potential therapeutic target for preventing damage caused by acute mitochondrial dysfunction in the lateral wall of the cochlea in rats. [116] As mentioned above, inflammation is the body's defensive response to stimuli to maintain homeostasis.…”
Section: Inflammation Dna Damage and Mitochondrial Imbalancementioning
confidence: 99%